Network Pharmacology and In Vitro Validation of Brazilin as a Potential Apoptosis-Inducing Agent in HBV-Related Hepatocellular Carcinoma - Hanifa, Mila; Utomo, Rohmad Yudi; Jenie, Riris Istighfari (Indonesian Society for Cancer Chemoprevention, 2024)
Hepatitis B virus (HBV) reactivation-related hepatocellular carcinoma (HCC) presents a significant threat due to its potential to cause liver failure and mortality. Consequently, the discovery of novel treatments that offer anticancer efficacy and liver protection is urgently needed. Brazilin, a natural compound, has previously been reported to possess cytotoxic and liver-protective properties. This research aimed to investigate the potency of brazilin in suppressing the growth of HCC cells through in silico and in vitro approaches. Hep3B cells, which harbor integrated HBV DNA, were selected as the HCC model, with PGV- 1 utilized as a positive control. The in silico study used network pharmacology to predict brazilin’s potential gene targets. Cytotoxicity was evaluated using the CCK-8 assay, and apoptosis detection was carried out using Annexin V/PI staining followed by flow cytometry. The analysis predicted that brazilin targets key genes such as SRC, EGFR, AKT1, GRB2, IGF1, ESR1, STAT1, MMP9, JAK2, and PPARG involved in cancer proliferation and metastasis. Proteins such as SRC, GRB2, and MMP9 are overexpressed in TP53-mutated HCC and linked to low survival. Brazilin showed moderate cytotoxicity with an IC50 value of 17 μM at 72 h and significantly induced apoptosis in Hep3B cells. These findings suggest that brazilin is a promising apoptosis-inducing agent for HBV-related HCC.Keywords: brazilin, Hep3B cell lines, network pharmacology, cytotoxic, apoptosis.